PENINGKATAN KREATIVITAS MELALUI METODE PEMBELAJARAN INKUIRI - Padilah, Padilah (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2018)
The purpose of this research was to describe the implementation process inquiry and to understand improving creativity of children 5-6 years old through inquiry. The study was conducted on group A Kindergarten with of seventen children. This study used action research methods by Kemmis and Taggart which consist of 4 stages (plan, action, observation and reflection). This study consisted of two cycles, each cycles consisting of 8 sessions. Data collecting techniques used observation, field notes and documentation. Data analysis using quantitative and qualitative data. Quantitative data analysis with descriptive statistics that compare the result obtained from the first cycle and the second cycle. Analysis of qualitative data by analizing data from the observation, fields notes and documentation during the study to the steps of data reduction, data display and data verification. The result of this study showed that there was the improving interpersonal intelegence through play music with score in pre cycle 24,9 had improvement to 44,9 and become 67,7 in cycle II and excellent growing category. Keywords : creativity, inquiry, Action Research